Plcγ2/Tmem178 dependent pathway in myeloid cells modulates the pathogenesis of cytokine storm syndrome. (June 2019) - Mahajan, Sahil; Decker, Corinne E.; Yang, Zhengfeng; Veis, Deborah; Mellins, Elizabeth D.; Faccio, Roberta
Abstract: Cytokine storm syndrome (CSS) is a life-threatening condition characterized by excessive activation of T cells and uncontrolled inflammation, mostly described in patients with familial hemophagocytic lymphohistiocytosis and certain systemic auto-inflammatory diseases, such as systemic juvenile idiopathic arthritis (sJIA). Defects in T cell cytotoxicity as a mechanism for uncontrolled inflammation following viral infections fail to represent the whole spectrum of CSS. Evidence implicates dysregulated innate immune responses, especially activation of monocytes and macrophages, in patients with CSS. However, the direct contribution of monocytes/macrophages to CSS development and the signaling pathways involved in their activation have not been formally investigated. We find that depletion of monocytes/macrophages during early stages of CSS development, by clodronate-liposomes or neutralizing anti-CSF1 antibody, reduces mortality and inflammatory cytokine levels in two CSS mouse models, one dependent on T cells and the second induced by repeated TLR9 stimulation. We further demonstrate that activation of Plcγ2 in myeloid cells controls CSS development by driving macrophage pro-inflammatory responses. Intriguingly, the Plcγ2 downstream effector Tmem178, a negative modulator of calcium levels, acts in a negative feedback loop to restrain inflammatory cytokine production. Genetic deletion of Tmem178 leads to pro-inflammatory macrophage polarization in vitro and more severe CSS in vivo . Importantly, Tmem178 levels are reduced in macrophages from mice with CSS and after exposure to plasma from sJIA patients with active disease. Our data identify a novel Plcγ2/Tmem178 axis as a modulator of inflammatory cytokine production by monocytes/macrophages. We also find that loss of Tmem178 accentuates the pro-inflammatory responses in CSS. Highlights: Activation of Plcγ2 pathway in monocytes/macrophages drives inflammation in CSS. Tmem178, a Plcγ2 downstream effector, is a negative regulator of inflammation. Loss of Tmem178 worsens CSS severity in two established CSS mouse models. Loss of Tmem178 drives a pro-inflammatory macrophage phenotype. Tmem178 levels are reduced in macrophages upon exposure to an inflammatory milieu.